The ethics of anger - Lewis, Court D.; Bock, Gregory L. (Lexington Books, 2020)
"This book provides a variety of diverse perspectives related to the ethics of anger, some more analytical in nature, others focused on practical issues, some in defense of anger, and others arguing against its necessity. This book is an essential resource for scholars who want to reflect critically on the place of anger in contemporary life"--